Application of Mechanistic Pharmacokinetic Model for the Optimization of Metformin Delayed Release Dosage Form for Intestinal Targeting - Malayandi, Rajkumar; Joseph, Anumol; Akbar, Sideequl; Natesan, Subramanian; Velayutham, Ravichandiran (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Metformin (MET) is a widely prescribed drug for managing Type 2 Diabetes Mellitus (T2DM). Despite the rich clinical experience and advantages, the clinical utility of MET in renal failure patients is limited because of the treatment-related side effects. A novel colon-targeted MET Delayed-Release (DR) dosage form could be a lucrative option for managing T2DM in renal failure patients. MET DR tablets have minimum systemic exposure and are believed to have the same efficacy as other formulations. Physiologically Based Pharmacokinetic (PBPK) modelling can be useful for drug product development, especially for new dosage forms for improving the safety, efficacy, and clinical applicability of off-patented generic drugs. Objectives The current study aims to develop a PBPK model for Proto-type (PT) screening of MET DR tablets. Materials and Methods MET PBPK model was developed based on the available literature data. Firstly, Intravenous (IV) and oral PBPK models of MET are developed and validated. The developed model was then used to predict the Bioavailability (BA) of PT MET DR tablets using Virtual Bioequivalence (VBE) trials. Results The relative bioavailability of the MET DR tablet was about 20% when compared with other MET formulations. The results indicate that the DR formulation could be effective for reducing the BA and systemic exposure of the drug in chronic renal failure patients. Conclusion PBPK modelling and VBE trials can successfully demonstrate the Pharmacokinetic (PK) parameters of PK formulations and the lower systemic exposure and site targeting of MET DR tablets could be useful for the management of T2DM in renal failure patients.
Keywords: Metformin; Delayed release; Renal failure; PBPK; Pharmacokinetics; Optimization